"Artists, We Need You": Artist Identity, Creative Agency, and the Urgency of Action. (3rd April 2021) - Travis, Sarah
Abstract : In this article, I examine the interplay of artist identity, creative agency, and the urgency of action through research with a teen arts internship at a contemporary arts center in post-Katrina New Orleans. The central research questions for the study focused on investigation of the contexts, narratives, activities, and consequences of artist identity formation. First, I offer a brief literature review of art education for social justice, activism, and creative agency. Then, I describe the use of social practice theory of identity and agency to interpret activist artist identity development within the research. Next, I delineate the use of portraiture as methodology to construct narrative portraits of the young artists of the study. Finally, I present data and analysis of the findings of the study of the contexts, narratives, activities, and consequences of activist artist identity work.